Fluctuation of Bone Marrow Lesions and Inflammatory MRI Markers over 2 Years and Concurrent Associations with Quantitative Cartilage Loss - Roemer, Frank W.; Jansen, Mylène P.; Maschek, Susanne; Mastbergen, Simon C.; Marijnissen, Anne Karien; Wisser, Anna; Heiß, Rafael; Weinans, Harrie H.; Blanco, Francisco J.; Berenbaum, Francis; Kloppenburg, Margreet; Haugen, Ida K.; et al. (Cartilage, 2024)
Objective: To assess whether change of semiquantitatively magnetic resonance imaging (MRI)-defined bone marrow lesions (BMLs) and inflammatory markers is associated with change in quantitatively-assessed cartilage loss in the femorotibial joint (FTJ) in knees with radiographic osteoarthritis (OA) over 24 months. Design: Participants were included from the IMI-APPROACH and the Osteoarthritis Initiative FNIH studies. Semiquantitative MRI assessment was performed for BMLs, Hoffa- and effusion-synovitis. Quantitative cartilage thickness measurements were performed manually. Definitions of change included number of subregions with BMLs, change in sum and change in maximum increase in size. Change in Hoffa-synovitis and effusion-synovitis was categorized in addition. Between-group comparisons regarding cartilage loss in the FTJ, medial and lateral compartments were performed using analysis of variance (ANOVA). Results: A total of 629 participants were included. Knees without any BMLs at baseline (BL) and follow-up (FU) had significantly less cartilage loss compared to the other subgroups. Change in both directions in the sum score of BMLs was associated with increased rates of cartilage loss. Maximum increase in size of BMLs was associated with increased rates of cartilage loss (FTJ increase by 2 grades −0.183 mm, 95% CI [−0.335, −0.031], by 3 grades −0.306 mm, [−0.511, −0.101]). Worsening of Hoffa-synovitis was associated with increased rates of cartilage loss. Conclusion: Knees without BMLs at BL and FU showed lowest rates of cartilage loss. Knees with an increase in BML size showed increased rates of concurrent cartilage loss. Approaches with the aim to inhibit BML development, avoidance of increase in size and avoidance of Hoffa-synovitis worsening may have beneficial effects on cartilage loss.
CRIS-Team Scopus Importer:2024-12-06
Keywords: bone marrow lesions; cartilage; knee; MRI; osteoarthritis